Multi stakeholder dialogue: Together Scaling Climate Smart Agriculture and Climate Information Services in Zambia - Mwale, Moses (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This presentation was made by the Director in the department of agriculture under the ministry of agriculture of Zambia. In his presentation, the Director highlighted climate challenges Zambia has experienced since the 1980s, including efforts made to reduce the vulnerability. He made the presentation during the launch of the CSA-CIS multi-stakeholder dialogue space; an initiative of the AICCRA Zambia project. AICCRA Zambia is a 3-year (2021-2023) initative led by the International Water Management Institute with funding from the International Development Association (IDA) of the World Bank to the Accelerating Impact of CGIAR Climate Research for Africa (AICCRA) project.